C60 and its derivatives at Si surfaces: experimental and theoretical studies of electronic structure - Phillips, Michael Andrew (2004)
There has been a considerable amount of research into the effects of the modifcation of C60 on its properties in the bulk and at metal surfaces. Strong covalent interactions between C60, its derivatives, and a silicon substrate, however, are not well understood, nor is their role in determining the electronic properties of a modified fullerene film. In conjunction with existing knowledge concerning the behaviour of unmodified C60 at silicon surfaces, the study of modified C60 at these surfaces may provide some insight into the nature of the adsorbate{substrate interactions. Furthermore, if the tunability o®ered by fullerene modification is to be exploited in the production of novel nanoscale devices, an understanding of the role of these interactions is of key importance.